A meta-analysis and meta-regression of long-term outcomes of transcatheter versus surgical aortic valve replacement for severe aortic stenosis. (15th December 2016) - Villablanca, Pedro A.; Mathew, Verghese; Thourani, Vinod H.; Rodés-Cabau, Josep; Bangalore, Sripal; Makkiya, Mohammed; Vlismas, Peter; Briceno, David F.; Slovut, David P.; Taub, Cynthia C.; McCarthy, Patrick M.; Augoustides, John G.; et al.
Abstract: Background: Transcatheter aortic valve replacement (TAVR) has emerged as an alternative to surgical aortic-valve replacement (SAVR) for patients with severe symptomatic aortic stenosis (AS) who are at high operative risk. We sought to determine the long-term (≥ 1 year follow-up) safety and efficacy TAVR compared with SAVR in patients with severe AS. Methods: A comprehensive search of PubMed, EMBASE, Cochrane Central Register of Controlled Trials, conference proceedings, and relevant Web sites from inception through 10 April 2016. Results: Fifty studies enrolling 44, 247 patients met the inclusion criteria. The mean duration follow-up was 21.4 months. No difference was found in long-term all-cause mortality (risk ratios (RR), 1.06; 95% confidence interval (CI) 0.91–1.22). There was a significant difference favoring TAVR in the incidence of stroke (RR, 0.82; 95% CI 0.71–0.94), atrial fibrillation (RR, 0.43; 95% CI 0.33–0.54), acute kidney injury (RR, 0.70; 95% CI 0.53–0.92), and major bleeding (RR, 0.57; 95% CI 0.40–0.81). TAVR had significant higher incidence of vascular complications (RR, 2.90; 95% CI 1.87–4.49), aortic regurgitation (RR, 7.00; 95% CI 5.27–9.30), and pacemaker implantation (PPM) (RR, 2.02; 95% CI 1.51–2.68). TAVR demonstrated significantly lower stroke risk compared to SAVR in high-risk patients (RR, 1.49; 95% CI 1.06–2.10); no differences in PPM implantation were observed in intermediate-risk patients (RR, 1.68; 95% CI 0.94–3.00). In a meta-regression analysis, the effect of TAVR baseline clinical features did not affect the long-term all-cause mortality outcome. Conclusion: TAVR and SAVR showed similar long-term survival in patients with severe AS; with important differences in treatment-associated morbidity. Highlights: TAVR and SAVR showed similar long-term survival in patients with severe AS. TAVR showed lower rate of stroke, acute kidney injury and atrial fibrillation compared to SAVR. TAVR showed higher rate of vascular complications, aortic regurgitation and pacemaker implantation compared to SAVR.